Composition, distribution and movement of howler monkey troops (Alouatta palliata) in the agricultural landscape of Pital, San Carlos, Costa Rica - Vargas-Alpízar, Paulina (2022)
Some areas intensively used by humans provide suitable habitat for wildlife, and knowledge of basic population characteristics of wildlife in these areas can help prioritize appropriate actions for their protection. The objective of the present study was to determine the distribution, composition and movement of troops of howler monkeys in an agricultural landscape of 8,400 ha in Pital of San Carlos, Costa Rica. This area contains a total of 115 forest fragments larger than 0.5 ha, of which 103 were evaluated, and 39 were occupied by monkeys. A total of 561 individuals were counted, for an ecological density of 1.44 individuals/ha. On average, troops were composed of 24% adult males, 45% adult females, 24% juveniles, and 7% infants. Most of reported monkey movements (76%) between fragments and through deforested areas covered less than 300 m. There is a positive relationship between increase in size and vegetation quality of the forest fragments with the number of howler monkeys found in the fragments. The high number of individuals encountered in this study, compared to that in other areas, may be related to the vegetation quality in fragments inside the study area or their surroundings.